Microforming - Geiger, Manfred; Kleiner, M.; Eckstein, Ralf; Tiesler, Nicolas; Engel, Ulf (Keynote Paper. Annals of the CIRP, 2001)
Microforming is a well suited technology to manufacture very small metallic parts, in particular for mass production, as they are required in many industrial products resulting from microtechnology. Compared to other manufacturing technologies microforming features specific economical and ecological advantages. Nevertheless, there are only some singular applications known until today. This paper tries to final out the reason why, analyzing systematically the problems emerging in transferring the know-how on forming from the macro- to the microworld. Reviewing the state of the art in basic and applied research reveals that scaling effects do appear not only within the process but must be taken into account in all the other areas of the whole forming system as well, demanding finally new solutions especially for tool manufacturing and machine concepts. Recent progress, innovative ideas and new developments on these sectors represent a promising basis to exploit the inherent potential of microforming in the future. © 2001 Elsevier Science Ltd. All rights reserved.
LFT Import::2019-08-05 (855)
Keywords: Equipment; Material; Micro Metal Forming